Characterization of gut microbiota in patients with metabolic syndrome candidates for bariatric/metabolic surgery: Preliminary findings of a multi-center prospective study. (October 2021) - De Maio, Flavio; Boru, Cristian Eugeniu; Avallone, Marcello; Velotti, Nunzio; Bianco, Delia Mercedes; Capoccia, Danila; Greco, Francesco; Guarisco, Gloria; Nogara, Manuela; Sanguinetti, Maurizio; Verrastro, Ornella; Capaldo, Brunella; et al.
Abstract: Introduction: gut microbiota (GM) seems to be involved in the pathophysiology and progression of both metabolic syndrome (MS) and obesity. The aim was to investigate GM's composition in patients with severe obesity, candidates for bariatric/metabolic surgery BMS. Materials and Methods: Multicentre, prospective, cohort study, enrolling 84 patients with BMI 40–55 kg/m 2, divided by metabolic status (MS) in healthy (group A), pre-MS (B), or MS (C). Results: No differences were found regarding anthropometric,  nutritional parameters, except for vitamin D. As a whole the alpha and beta diversity examinations showed no statistical differences in GM profile. A total of 5/7 phyla with relative frequencies were identified above 0.1% ( Actinobacteria,   Bacteroidetes,   Firmicutes,   Proteobacteria,   Verrucomicrobia) .  Fusobacteria  and  Patescibacteria  represented the less abundant. There were no significant differences in the top ten genera. Data on  Bacteroidetes  (inversely related to triglycerides and LDL and directly related to HDL levels) and on  Firmicutes  (opposite trend) relative abundances suggest no differences among the three conditions. No correlation between the relative abundance of the main phyla and plasmatic glucose levels was observed. Conclusions: In a selected cohort of patients with obesity, MS did not affect the preoperative GM's profile. Severe obesity, per se, seems to be an independent condition affecting GM.